Pengaruh Faktor Ekonomi, dan Penyelesaian Tindak Pidana Terhadap Tingkat Kejahatan Pencurian di Pulau Sumatera - Heru Wahyudi; Abdirrohman Abdirrohman (Jurnal Studi Ilmu Sosial dan Politik, 2021)
Purpose: This study aims to analyze the effect of economic inequality, open unemployment rate, poverty line, and crime clearence on criminal property rate in the provinces of Sumatra. Research methodology: The analytical method used in this study is OLS (Ordinary Least Square). This study uses panel data from 2010 - 2019 in 10 provinces in Sumatra using the FEM (Fixed Effect Model) model. Results: The results showed that the variables of economic inequality and proverty line had a positive significant effect on criminal property rate in Sumatera. Meanwhile, the open unemployment rate variable has a positive but not significant effect on criminal property rate in Sumatera, and the crime clearence has a significant negative effect on criminal property rate in Sumatera. Limitations: The limitation in this study is the use of a less specific poverty line variable. Contribution: The results obtained from this study are expected to be one of the references in making policy directions based on the data presented to adjust the right policies, especially to reduce the crime rate of theft on the island of Sumatra.